Gut microbiome and NAFLD: impact and therapeutic potential - Li, Liwei; Cai, Fuqing; Guo, Chen; Liu, Zheng; Qin, Jiamin; Huang, Jiean (Frontiers in Microbiology, 2024)
Non-Alcoholic Fatty Liver Disease (NAFLD) affects approximately 32.4% of the global population and poses a significant health concern. Emerging evidence underscores the pivotal role of the gut microbiota—including bacteria, viruses, fungi, and parasites—in the development and progression of NAFLD. Dysbiosis among gut bacteria alters key biological pathways that contribute to liver fat accumulation and inflammation. The gut virome, comprising bacteriophages and eukaryotic viruses, significantly shapes microbial community dynamics and impacts host metabolism through complex interactions. Similarly, gut fungi maintain a symbiotic relationship with bacteria; the relationship between gut fungi and bacteria is crucial for overall host health, with certain fungal species such as Candida in NAFLD patients showing detrimental associations with metabolic markers and liver function. Additionally, the “hygiene hypothesis” suggests that reduced exposure to gut parasites may affect immune regulation and metabolic processes, potentially influencing conditions like obesity and insulin resistance. This review synthesizes current knowledge on the intricate interactions within the gut microbiota and their associations with NAFLD. We highlight the therapeutic potential of targeting these microbial communities through interventions such as probiotics, prebiotics, and fecal microbiota transplantation. Addressing the complexities of NAFLD requires comprehensive strategies that consider the multifaceted roles of gut microorganisms in disease pathology.